Goal for gold, analyzing the impact of publicly listed football club match outcome on abnormal returns - Mohd Isa, Luqman Hakim (2020)
This paper investigates the impact of football matches results on respective abnormal returns in the stock market. A total of 5,530 matches of eleven publicly listed European football club in seven stock exchange between 2009-2019 was analysed by applying OLS method with five different models. These clubs are separated into two group with similar structure and ranks where group 1 are football club from “big four” nations and group 2 are from smaller countries. Other components included in the models such as the match venue, type of competition (national or European), expectation (betting odds) and timeframe (2009- 2014 and 2015-2019).